1998
DOI: 10.1046/j.1460-9592.1998.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Convective warming blankets improve peroperative heat preservation in congenital heart surgery

Abstract: Peroperative heat preservation, following hypothermic cardiopulmonary bypass (CPB) in children, has always been a challenge to the anaesthetist. We studied the efficiency of a convective heating system on peroperative heat preservation in 50 children undergoing congenital heart surgery. Twenty-five children, rewarmed by CPB and heating mattress, were randomly selected (Group 1). Another 25 children, rewarmed by CPB, heating mattress and convective warming blankets in addition (Group 2), were selected so the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This finding concurs with results obtained with human subjects during various surgical operations in adults (Lennon et al 1990;Hynson and Sessler 1992;Russell et al 1995) and in children (Kurz et al 1993;Schlunzen et al 1998). In neonates, Komatsu et al (1996) and Asaga et al (1997) reported that the forced-air warming system with a ringshaped cover is an effective method for maintaining homeothermia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding concurs with results obtained with human subjects during various surgical operations in adults (Lennon et al 1990;Hynson and Sessler 1992;Russell et al 1995) and in children (Kurz et al 1993;Schlunzen et al 1998). In neonates, Komatsu et al (1996) and Asaga et al (1997) reported that the forced-air warming system with a ringshaped cover is an effective method for maintaining homeothermia.…”
Section: Discussionsupporting
confidence: 92%
“…However, heat is supplied only to the parts of the patient in contact with the mattress. Convective warming blankets are an effective method for preventing hypothermia in children during congenital heart surgery (Schlunzen et al 1998) and in adult patients during orthotopic liver transplantation (Russell et al 1995) or major maxillofacial surgery (Kurz et al 1993). However, warming neonates via heat conduction through a mattress remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…(8) described benefit of convection heating over radiant in rewarming 24 children after cardiac bypass procedures. Subsequent reports have been disappointing either because they were: retrospective reviews [(9) 25 children having cardiac bypass surgery], gave almost no details about methodology – including technique of warming – device, temperature and so [(10) 10 children, (2) 17 neonates, correspondence] or used techniques known to give inaccurate results (3,10). Szmuk et al.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it might be questionable as to whether or not the results found in this study are relevant to human beings. On the other hand, we should question whether or not the results from adult patients, such as those which show the advantage of fast rewarming on trauma patients with moderate hypothermia (27), are applicable for the paediatric age group under the same conditions (20).…”
Section: Discussionmentioning
confidence: 99%
“…A rate of 1.0 °C·h –1 and rewarming as rapidly as possible, with adequate tissue perfusion, were found to be beneficial (15,24–26). The anaesthesia literature discusses the benefits of different strategies of heating patients recovering from cardiac surgery (27–30). In order to determine the influence of various rewarming rates following acute moderate hypothermia, a model in rats was established and two modes of rewarming rates (fast and slow) were evaluated.…”
Section: Introductionmentioning
confidence: 99%